BACLOFEN UNUSUAL RESPONSE IN SPINAL CORD INJURY PATIENTS - Ullah, Sami; Edrees, Maha; Alhabtar, Ahmad Mushabbab (Journal of Ayub Medical College Abbottabad, 2019)
Spasticity after spinal cord injury (SCI) is a major problem that can limit the effectiveness of rehabilitation programs. Oral baclofen is more frequently used in treating spasticity than other antispasmodic agents due to its proven overall efficacy. Herein, we are reporting two SCI patients who reported unusual response to baclofen. Case 1 (28-year-old male) his injury was classified as T3 AIS-A. Case 2 (36-year-old male) his injury was classified as T4 AIS-A. Both cases reported worsening of spasms with the initiation of baclofen and the rapid improvement upon discontinuing the medication. The effect was dose-dependent as reported by both of our patients. Our impression is a rebound spasm secondary to baclofen as evident by the severity of spasm and spasticity that were directly proportional to the baclofen dose. Awareness of this reversible side effect is essential for its management. Moreover, it might provide a clue to understanding the mechanism of action of baclofen. Keywords: Spasticity; Spasms; Baclofen; Spinal Cord Injury; Rehabilitation; Case Series